2013
DOI: 10.1111/cts.12072
|View full text |Cite
|
Sign up to set email alerts
|

Community Representatives’ Involvement in Clinical and Translational Science Awardee Activities

Abstract: Objectives: To understand the formal roles of community representatives (CRs) in Clinical and Translational Science Awardee (CTSA) activities, to evaluate the extent of integration into the organizational and governance structures and to identify barriers to effective integration.Methods: The inventory tool was distributed to each of the 60 CTSAs using a secure web application.Results: Forty-seven (78%) completed the inventory. The mean number of CRs per CTSA is 21.4 (SD: 14.8). Most CTSAs had community adviso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 10 publications
(18 reference statements)
1
54
0
Order By: Relevance
“…19 It also shows the efficacy of drawing on community partners’ own skill sets to strengthen the collaboration, providing opportunities for leadership, which are often limited in such engagements. 23 …”
Section: Discussionmentioning
confidence: 99%
“…19 It also shows the efficacy of drawing on community partners’ own skill sets to strengthen the collaboration, providing opportunities for leadership, which are often limited in such engagements. 23 …”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the study, the function of a CAB is vastly different. In some cases, they meet infrequently and their involvement is limited (Wilkins et al, 2013). In contrast, some studies work intensively with a CAB, with the CAB having more authority in determining the next research agenda, almost like a community partner in a CBPR model (Cooper, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These awards were initiated and tied to a significant funding stream, to provide training and research support for up to 60 medical schools for translational science—from proof‐of‐concept studies, to efficacy and effectiveness studies, to behavioral research and community engagement. However, a recent study among community engagement stakeholders expressed skepticism about the current role of the community in the CTSA program because the requirement for engaging the community has been removed from the most recent funding announcement, and other studies have found a reduced role for the community in CTSA leadership activities …”
Section: Addressing Persistent Chronic Disease Prevalence Through Commentioning
confidence: 99%